Aluminiumlösungen aus maßgeschneidert wärmebehandelten Halbzeugen - Graser, Matthias; Degner, Julia; Böhm, Wolfgang; Merklein, Marion (Konstruktion, 2017)
LFT Import::2019-07-29 (2271)

Characterisation of new lubrication systems for hot forming of high strength aluminum alloys - Rigas, Nikolaos; Degner, Julia; Berendt, E.; Junker, F.; Merklein, Marion (OP Conference Series, Materials Science and Engineering, 2019)
LFT Import::2019-08-05 (2381)

Efficient Aluminium - Anwendung hochfester Aluminiumlegierungen im modernen Karosseriebau - Degner, Julia; Merklein, Marion (Tagungsband des 37. EFB-Kolloquiums Blechverarbeitung 2017, 2017)
LFT Import::2019-08-05 (2223)

Experimental study on the flow behavior during hot forming and quenching of the high-strength aluminum alloy AA6111 - Degner, Julia; Horn, Alexander; Merklein, Marion (XXXVI. Verformungskundliches Kolloquium, 2017)
LFT Import::2019-08-05 (2221)

Experimental study on the warm forming and quenching behaviour for hot stamping of high-strength aluminum alloys - Degner, Julia; Horn, Alexander; Merklein, Marion (Journal of Physics: Conference Series, 2017)
LFT Import::2019-08-05 (2228)

Grundlegende Untersuchungen zur Herstellung hochfester Aluminiumblechbauteile in einem kombinierten Umform- und Abschreckprozess - Degner, Julia (Friedrich-Alexander-Universität Erlangen-Nürnberg, 2020)
Mobility is the prerequisite for the economic and social development of our modern service and industrial society.To guarantee mobility also in the future, sustainable measures and strategies are needed to increase the effi-ciency of vehicles while at the same time reducing environmental pollution, such as CO2 emissions. One of these strategies is the weight reduction of vehicles based on light-weight strategies and materials. Due to the high strength and low density, the focus of research has recently been on high-strength aluminum alloys, as these can lead to further sheet thickness reductions compared to conventional aluminum alloys and realize light-weight constructions even in safety- and crash-relevant areas. However, the challenge is the limited formability of these alloys, which is why tempera-ture-assisted forming processes are usually used. A new approach is the combined forming and quenching process. By means of a heat treatment in combination with an immediate forming and simultaneous quenching, the production of sophisticated component geometries can be enabled, which in turn can be optimized to the highest strengths by means of ageing pro-cesses. The aim of this work was to generate a basic process understanding for the manufacturing of high-strength aluminum sheet metal components within the framework of a combined forming and quenching process. The focus was on the definition of boundary conditions during heat treatment on the basis of a sensitivity analysis, the process design based on a thermal and mechanical material characterization as well as the process analysis and evaluation to identify the potential of a combined forming and quench-ing process using a demonstrator componen

Influence of Pre-Strain and Simulated Paint-Bake on Mechanical Properties of High Strength Aluminium Alloy AA7020 - Merklein, Marion; Degner, Julia (Applied Mechanics and Materials, 2015)
LFT Import::2019-07-29 (2122)

Investigation of the Unloading Yield Effect in Aluminum and Magnesium Sheet Metal Alloys at Room Temperature - Degner, Julia; Suttner, Sebastian; Merklein, Marion (Key Engineering Materials, 2016)
LFT Import::2019-07-29 (2178)
Keywords: Advanced Lightweight Materials; Material Characterization; Unloading Yield

Leichtbauwerkstoffe für den modernen Automobilbau - Degner, Julia; Herrmann, Jürgen; Junker, Friedhelm; Berendt, Erik; Merklein, Marion (Konstruktion, 2018)
LFT Import::2019-07-29 (2296)

Manufacturing and Characterization of Multilayered 7000-Series Aluminum with Improved Corrosion Behavior Processed via Accumulative Roll Bonding - Degner, Julia; Bohm, Wolfgang; Herrmann, Jürgen; Kohler, Markus; Merklein, Marion (MATERIALS TODAY-PROCEEDINGS, 2019)
CRIS-Team WoS Importer:2019-04-12

Manufacturing of Innovative Aluminum Components by Combining Shear Cutting Operation and Tailor Heat Treated Blank Technique - Degner, Julia; Suttner, Sebastian; Tsoupis, Ioannis; Lechner, Michael; Merklein, Marion (5th International Conference on Accuracy in Forming Technology, 2015)
LFT Import::2019-08-05 (2130)

Maßgeschneiderte Halbzeuge - Umformtechnische Herstellung von Funktionsbauteilen zur Realisierung von Leichtbaukomponenten - Hetzel, Andreas; Schulte, Robert Karl; Vogel, Manfred; Degner, Julia; Merklein, Marion (wt Werkstattstechnik - Online, 2019)
Sheet Bulk Metal Forming enables the efficient manufacturing of functional lightweight components with different functional elements in a combined single stage deep drawing and upsetting process. By investigating the forming results with a conventional blank, regarding the properties like grain structure and Vickers hardness distribution, process limitations such as buckling and folding can be detected. These failures occur due to a three-dimensional stress and strain state as well as an insufficient die filling. A significant improvement of the quality of the produced parts can be enabled by the use of Tailored Blanks in the investigated process chain. With the manufacturing of the semi-finished parts by orbital forming, an adapted material pre-distribution can be realized, thus improving the die filling followed by a decrease of the parts' failures. Current research at the Institute of Manufacturing Technology focuses on the extension of the applicability of Tailored Blanks.
CRIS-Team Scopus Importer:2020-02-21

Microstructural evolution and geometrical properties of TiB2 metal matrix composite protrusions on hot work tool steel surfaces manufactured by laser implantation - Spranger, Felix; de Oliveira Lopes, Marcelo; Schirdewahn, Stephan; Degner, Julia; Merklein, Marion; Hilgenberg, Kai (International Journal of Advanced Manufacturing Technology, 2019)
The laser implantation–named technique aims to address the tribological problems frequently seen on tool surfaces during hot stamping. It is based on the creation of elevated dome- or ring-shaped hard structures on the surface of tool steels by a localized dispersing of hard particles. Therefore, a combination of the two distinct approaches that are normally used in surface technology for optimizing friction and wear, i.e., surface texturing and surface material optimization, are realized in one processing step. In experimental studies, a localized dispersing of TiB2 particles in the surface layer of the hot work tool steel X38CrMoV5-3 was considered and compared with punctual laser–remelted textures. The structures (micro-) hardness was measured at top- and cross-sections. With the aid of a scanning electron microscope, energy dispersive X-ray spectroscopy and X-ray diffraction the interaction between the hard particles and the substrate material were studied. From the results, an optimal parameter range was identified for laser implantation. To the investigation’s end, the implant geometry was measured by optical microscopy and white light microscopy. Furthermore, a mathematic model was introduced, which allows a prediction of the implant geometry as a response to the laser parameters. It was shown that the implantation of TiB2 particles leads to a significant hardness increase up to 1600 HV1 due to the dispersion of initial particles and an in situ precipitation of new titanium-rich phases. It was possible to create defect-free dome- and ring-shaped microstructures on the surfaces. It was also shown that the implants geometry highly depends on the applied laser parameters. The applied central composite design shows a good agreement with the experimental results.
CRIS-Team Scopus Importer:2019-12-03
Keywords: Hot stamping; Hot work tool steel; Laser implantation; Localized laser dispersing; Surface texturing; TiB2

Numerical Investigation for Superplastic Forming Tool Development Within the Combined Process Chain of Forming and Additive Manufacturing - Schaub, Adam; Degner, Julia; Ahuja, B.; Schmidt, M.; Merklein, Marion (Int. Conf. Competitive Manufacturing, 2016)
Key motivation behind the combination of superplastic forming and additive manufacturing is to merge the advantages of two different manufacturing methods. On the one hand the efficiency to form large scaled parts by superplastic forming and on the other hand additive manufacturing of highly customised products. While the combination of additive manufacturing with bulk structures is state of the art, combining sheet metal parts with additive functional elements is hardly investigated. Few research works have been published regarding additively manufactured functional elements on deep drawn sheet parts. As forming is limited for Ti-6Al-4V at room temperature and even at moderate temperatures, this paper presents a new and innovative manufacturing process chain, where superplastic forming and additive manufacturing is combined to merge the advantages of both. Within this work the possibilities of additive manufacturing on sheet metal is presented in addition to the numerical simulation of superplastic forming of Ti-6Al-4V to produce a semi-finished sheet part for subsequent additive manufacturing process. As a result of this study a LS-DYNA based numerical model is presented for tool development as well as process simulation for superplastic forming of semi-finished parts which can be utilized for consecutive additive manufacturing operation.<br
LFT Import::2019-08-05 (2154)
Keywords: Superplastic Forming; Additive Manufacturing; Ti-6Al-4V

Numerische Auslegung eines kombinierten Umform- und Abschreckprozesses zur Herstellung hochfester Aluminiumbauteile - Degner, Julia; Merten, M.; Merklein, Marion (Tagungsband zum 13. Erlanger Workshop Warmblechumformung 2018, 2018)
LFT Import::2019-08-05 (2350)

Process Design of Aluminum Tailor Heat Treated Blanks - Kahrimanidis, Alexander; Lechner, Michael; Degner, Julia; Wortberg, Daniel; Merklein, Marion (Materials, 2015)
LFT Import::2019-07-29 (2141)
Keywords: Lightweight design; Material model; Tailor heat treated blanks

Scale-up of Innovative Forming Solutions from Scientific Fundamentals to Industrial Applications - Merklein, Marion; Lechner, Michael; Böhm, W.; Degner, Julia (2016)
LFT Import::2019-08-05 (2219)

Tailoring material properties in forming technology by a local heat treatment - Merklein, Marion; Graser, Matthias; Degner, Julia; Lechner, Michael; Herrmann, Jürgen (Advanced Metal Forming Processes in Automotive Industry, 2016)
LFT Import::2019-08-05 (2177)

Verbesserung der Umformbarkeit von Aluminium - Graser, Matthias; Degner, Julia; Böhm, Wolfgang; Merklein, Marion (Konstruktion, 2017)
CRIS-Team Scopus Importer:2023-03-29